Kajian Penggunaan Nutrisi Anorganik terhadap Pertumbuhan Kangkung (Ipomoea reptans Poir) Hidroponik Sistem Wick - Nurul Hidayati; Pienyani Rosawanti; Fitriadi Yusuf; Nanang Hanafi (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2017)
This study aims to determine the effect of giving different types of nutrients on the growth of kale in hydroponic wick system. The study was a single factor experiment with two treatments using Completely Randomized Design (CRD) with 7 replications. The treatment given was inorganic fertilizer AB Mix and NPK plus inorganic fertilizer. Nutritional concentration was given as much as 10 ml/liter. The results showed that the type of nutrient treatment was significantly affected the growth of plant height at age 14 days after planting (DAP) and 21 DAP. At age 28 DAP there was no real effect. The producing of leaves number was differences at all stages. Provision of nutrition AB mix produced higher plant height at 14 DAP (15.9 cm) and 21 DAP (19.3 cm). The parameter of leaf number, AB mix yield more leaves at 14 hst (8,1 strand), 21 hst (11,1 strands) and 28 DAP (13,4 strands) respectively.